Protective effect of panaxydol against repeated administration of aristolochic acid on renal function and lipid peroxidation products via activating Keap1‐Nrf2/ARE pathway in rat kidney. Issue 1 (7th September 2020) - Guo, Yinxue; Hu, Maorong; Ma, Juan; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Shair, Omar H. M.; Ge, Pingyu
Abstract: Panaxydol (PX), a polyacetylenic compound isolated from the roots of Panax notoginseng, is found to possess various biological functions. However, its protective effects against aristolochic acid (AA)‐induced renal injury have not been elucidated yet. The present study was undertaken to elucidate the renoprotective effect of PX on Wistar male rats via activating Keap1‐Nrf2/ARE pathway. Experimental animals were randomized into four groups, such as control group, I/R group, AA (5 mg/kg/d; ip for 10 days), and AA‐induced rats treated with PX (10 and 20 mg/kg/d; po for 20 days). At the end of the experimental period, the rats were killed, and the biochemical parameters denoting renal functions were evaluated; histological analysis displaying the renal tissue architecture, real‐time quantitative reverse‐transcription polymerase chain reaction, and immunohistochemistry (IHC) analysis of Keap1‐Nrf2/ARE genes were elucidated. The results demonstrated that the rats administered with AA displayed a significant increase in the blood urea nitrogen level with an increased urine creatinine and protein excretion. Also, the serum levels of urea, uric acid, and albumin levels were increased. Furthermore, the histological evaluation denoted the cellular degeneration with increased tissue lipid peroxidation levels. In contrast, rats administered with PX significantly prevented the tissue degeneration with improved antioxidant levels. Conversely, PX treatment increased the messenger RNA expression of Nrf2, NQO1, HO‐1 with an attenuated expression of 4HNE and NOX‐4 levels in IHC analysis. Thus, the results of the present study suggest that PX could suppress AA‐induced renal failure by suppressing oxidative stress through the activation of Keap1‐Nrf2 signaling pathway.